13.3% efficient solution deposited Cu(In, Ga)Se2 solar cells processed with different sodium salt sources. (27th November 2015) - Berner, Ulrich; Colombara, Diego; de Wild, Jessica; Robert, Erika V.C.; Schütze, Martin; Hergert, Frank; Valle, Nathalie; Widenmeyer, Markus; Dale, Phillip J.
Abstract: In this work, we obtain the highest reported power conversion efficiency (13.3%) for sulfur‐free CIGSe solar cells by solution processing. Intentional sodium incorporation is achieved directly by dissolving sodium salts in the ink. The effect on solar cell properties of three sodium sources is investigated: NaCl, NaHCO2, and NaSCN. A comparison is made with absorbers grown on soda‐lime glass substrates and in the absence of sodium sources. The incorporation via sodium salts yields significantly better results, which is attributed to enhanced‐sodium availability. A comparison with identically annealed sputtered metal precursor layers capable of delivering 15.1% module efficiency suggests that the cell results are limited by the selenization procedure. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The influence of three different Na salts (NaCl, NaHCO2, and NaSCN) dissolved together with the Cu, In and Ga precursors in a solution‐based approach for Cu(In, Ga)Se2 solar cells has been investigated. All salts improve the optoelectronic properties of the CIGSe devices, but NaHCO2 results in a lower increase of performance, due to reduced gallium incorporation, compared with NaSCN and NaCl. With NaCl and an optimized annealing procedure, a maximum efficiency of 13.3% (without ARC) could be achieved.